Quantitative analysis of pulmonary vasculature in systemic sclerosis at spirometry-gated chest CT. Issue 9 (30th June 2020) - Occhipinti, Mariaelena; Bruni, Cosimo; Camiciottoli, Gianna; Bartolucci, Maurizio; Bellando-Randone, Silvia; Bassetto, Anna; Cuomo, Giovanna; Giuggioli, Dilia; Ciardi, Giulia; Fabbrizzi, Alessio; Tomassetti, Sara; Lavorini, Federico; et al.
Abstract : Objective: To prospectively investigate whether differences in pulmonary vasculature exist in systemic sclerosis (SSc) and how they are distributed in patients with different pulmonary function. Methods: Seventy-four patients with SSc undergoing chest CT scan for interstitial lung disease (ILD) screening or follow-up were prospectively enrolled. A thorough clinical, laboratory and functional evaluation was performed the same day. Chest CT was spirometry gated at total lung capacity and images were analysed by two automated software programs to quantify emphysema, ILD patterns (ground-glass, reticular, honeycombing), and pulmonary vascular volume (PVV). Patients were divided in restricted (FVC% <80, DLco%<80), isolated DLco% reduction (iDLco- FVC%≥80, DLco%<80) and normals (FVC%≥80, DLco%≥80). Spearman ρ, Mann-Whitney tests and logistic regressions were used to assess for correlations, differences among groups and relationships between continuous variables. Results: Absolute and lung volume normalised PVV (PVV/LV) correlated inversely with functional parameters and positively with all ILD patterns (ρ=0.75 with ground glass, ρ=0.68 with reticular). PVV/LV was the only predictor of DLco at multivariate analysis (p=0.007). Meanwhile, the reticular pattern prevailed in peripheral regions and lower lung thirds, PVV/LV prevailed in central regions and middle lung thirds. iDLco group had a significantly higher PVV/LV (2.2%) than normal (1.6%), but lower than restricted ones (3.8%). Conclusions: Chest CT in SSc detects a progressive increase in PVV/LV as DLco decreases. Redistribution of perfusion to less affected lung regions rather than angiogenesis nearby fibrotic lung may explain the results. Further studies to ascertain whether the increase in PVV/LV reflects a real increase in blood volume are needed.